The Use of Trace Fossils in Delineating and Interpreting Stratigraphic Discontinuities - S. George Pemberton; James A. MacEachern; Murray K. Gingras (Berita Sedimentologi, 2004)
Trace fossils represent both sedimentological and palaeontological entities and as such, represent a unique blending of potential environmental indicators in the rock record. Trace fossils and trace fossil suites can be employed effectively to aid in the recognition of various discontinuity types and to assist in their genetic interpretations. Ichnology may be employed to resolve surfaces of stratigraphic significance in two main ways: 1) through the identification of discontinuities using substrate-controlled ichnofacies (i.e., the firmground Glossifungites ichnofacies, the hardground Trypanites ichnofacies, and the woodground Teredolites ichnofacies), and 2) through careful analysis of vertical softground (penecontemporaneous) ichnologic successions (analogous to facies successions). Integrating the data derived from substrate-controlled ichnofacies (so-called omission suites) with palaeoecological data from vertically and laterally juxtaposed softground ichnological successions greatly enhances the recognition and interpretation of a wide variety of potentially significant stratigraphic surfaces.